Contamination Control for Ultra-Sensitive Life-Detection Missions - Eigenbrode, Jennifer L.; Gold, Robert; Canham, John S.; Schulze, Erich; Davila, Alfonso F.; Seas, Antonios; Errigo, Therese; Kujawa, Faith; Kusnierkiewicz, David; Lorentson, Charles; McKay, Christopher (Frontiers in Space Technologies, 2021)
A key science priority for planetary exploration is to search for signs of life in our Solar System. Life-detection mission concepts aim to assess whether or not biomolecular signatures of life are present, which requires highly sensitive instrumentation. This introduces greater risk of false positives, and perhaps false negatives. Stringent science-derived contamination requirements for achieving science measurements on life-detection missions necessitate mitigation approaches that minimize, protect from, and prevent science-relevant contamination of critical surfaces of the science payload and provide high confidence to life-detection determinations. To this end, we report on technology advances that focus on understanding contamination transfer from pre-launch processing to end of mission using high-fidelity physics in the form of computational fluid dynamics and sorption physics for monolayer adsorption/desorption, and on developing a new full-spacecraft bio-molecular barrier design that restricts contamination of the spacecraft and instruments by the launch vehicle hardware. The bio-molecular barrier isolates the spacecraft from biological, molecular, and particulate contamination from the external environment. Models were used to evaluate contamination transport for a designs reference mission that utilizes the barrier. Results of the modeling verify the efficacy of the barrier and an in-cruise decontamination activity. Overall mission contamination tracking from launch to science operations demonstrated exceptionally low probability on contamination impacting science measurements, meeting the stringent contamination requirements of femtomolar levels of compounds. These advances will enable planetary missions that aim to detect and identify signatures of life in our Solar System.